Reducing the risk of food and nutrition insecurity among vulnerable populations - Geleta, Bekele; Ameri, Goli; Amdemariam, Kiflemariam; Fan, Shenggen; Stein, Alexander J.; Olofinbiyi, Tolulope (International Federation of Red Cross and Red Crescent Societies, 2012)
Vulnerable populations are minimally resilient to shocks, whether caused by humans or natural disasters. Emerging threats and new trends—such as climate change, population growth, aging societies, urbanization, infectious as well as noncommunicable diseases, and environmental degradation—are bound to aggravate the consequences of shocks on already vulnerable populations by triggering damage, loss, and displacement. Such threats pose an additional hurdle to the stated policy objective of the international community to eradicate hunger and malnutrition.